2010
DOI: 10.2165/11535390-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Tapentadol Immediate Release (IR) in Healthy Subjects and Patients with Moderate or Severe Pain

Abstract: The population pharmacokinetic model for tapentadol IR identified the relationship between pharmacokinetic parameters and a wide range of covariates. The simulations of tapentadol exposure with identified, statistically significant covariates demonstrated that only hepatic function (as characterized by total bilirubin and total protein) may be considered a clinically relevant factor that warrants dose adjustment. None of the other covariates are of clinical relevance, nor do they necessitate dose adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…Central volume of distribution (V 1 /F) had a statistically significant influence on creatinine clearance (CL CR ), with the former tending to decrease as the latter increases. Pharmacokinetic modeling and simulations showed that the effect of changes in creatinine clearance of a subject is estimated to result in < 10% change in tapentadol C max and AUC [30]. This finding supports the results of a Phase I study on patients with renal impairment, where the AUC and C max of tapentadol was comparable in subjects with different degrees of renal function impairment [6].…”
Section: Pharmacokinetics and Metabolismsupporting
confidence: 79%
See 2 more Smart Citations
“…Central volume of distribution (V 1 /F) had a statistically significant influence on creatinine clearance (CL CR ), with the former tending to decrease as the latter increases. Pharmacokinetic modeling and simulations showed that the effect of changes in creatinine clearance of a subject is estimated to result in < 10% change in tapentadol C max and AUC [30]. This finding supports the results of a Phase I study on patients with renal impairment, where the AUC and C max of tapentadol was comparable in subjects with different degrees of renal function impairment [6].…”
Section: Pharmacokinetics and Metabolismsupporting
confidence: 79%
“…It was demonstrated that body weight has a statistical significance on the apparent oral clearance (CL/F). The difference in pharmacokinetic parameters of the drug does not exceed more than 20% in correlation with body weight [30,31]. Subjects with low body weight (£ 50 kg, the 5th percentile of the population) had a 25% increase in C max and AUC values compared to subjects with high body weight (approximately 120 kg, the 95th percentile of the population) that demonstrated a decrease of 20%.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 90%
See 1 more Smart Citation
“…Tapentadol should be used with caution and reduced dosage in patients with moderate hepatic impairment and is not recommended for use in severe hepatic impairment. [19] It is advisable to start with lower range of recommended doses in elderly patients.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Analysis of serum pharmacokinetic samples from 1,827 healthy subjects and patients with moderate or severe pain demonstrated that among the covariates of sex, age, body weight, race, body fat, and hepatic function, only hepatic function may be considered a clinically relevant factor that warrants dose adjustment. 32 Two randomized, open-label, crossover studies of healthy adults demonstrated that no clinically relevant changes in serum concentrations of tapentadol occurred, and no dose adjustments were recommended for the administration of tapentadol concomitantly with acetaminophen, naproxen, or acetylsalicylic acid. 33 This characteristic is particularly advantageous, given the current emphasis on multimodal analgesia and specifically combining nonopioid analgesics with other agents for the treatment of pain.…”
Section: Adverse Effects and Precautionsmentioning
confidence: 99%